Long-term treatment outcome of Castleman’s disease: A real-world experience - Min, Gi-June; Jeon, Young-Woo; Kim, Tong Yoon; Kwag, Dae Hun; Lee, Jong Hyuk; Lee, Joon Yeop; Park, Sung-Soo; Park, Silvia; Yoon, Jae-Ho; Lee, Sung-Eun; Cho, Byung-Sik; Eom, Ki-Seong; et al. (Frontiers in Oncology, 2022)
Background: Castleman disease (CD), classified as unicentric CD (UCD) or multicentric CD (MCD), is a rare non-neoplastic lymphoproliferative disorder of unknown origin. Owing to its rarity, the clinical characteristics, therapeutic modalities, treatment outcomes, and prognostic factors related to UCD or MCD are not well defined. Method: We retrospectively analyzed 88 patients with CD, including those with hyaline-vascular, plasma-cell, mixed type, hypervascular, and plasmablastic subtypes, for presenting symptoms, physical, laboratory, and radiologic findings, and treatment response in the Korean population. Results: The median patient age was 44 years (range: 18–84 years) with slight predominance of women (53.4%). UCD and MCD accounted for 38.6% (n=34) and 61.4% (n=54) of cases, respectively. Histopathologically, UCD patients were classified as 88.2% (n=30) hyaline-vascular and 11.8% (n=4) plasma cell types, whereas MCD patients were classified as 27.8% (n=15) hypervascular, 61.1% (n=33) plasma cell, 7.4% (n=4) mixed, and 3.7% (n=2) plasmablastic types. Twelve (13.6%) patients exhibited a poor performance status with an Eastern Cooperative Oncology Group score of 2. The most common presenting symptom was sustained fever, followed by fatigue, anorexia, peripheral edema, and weight loss. Furthermore, splenomegaly, pleural effusion, and ascites were observed to be associated with CD. Surgical resection and siltuximab were the preferred treatment modalities for UCD and MCD, respectively, with favorable symptomatic, laboratory, and radiologic outcomes and safety profiles. The overall survival was 90.2%, with no significant difference between the UCD and MCD groups (p=0.073), but progression-free survival was significantly poorer in the MCD group (p=0.001). Age ≥60 years and splenomegaly significantly affected the overall and progression-free survival rates. Conclusion: Patients with UCD had favorable outcomes with surgical resection of a solitary mass, whereas in patients with MCD, old age and splenomegaly were identified as independent prognostic factors. Further well-designed prospective studies under advancing knowledge of the pathophysiology of MCD are warranted to establish suitable guidelines for the discontinuation or prolonging infusion intervals of siltuximab and treatment modalities for HHV-8 positive MCD patients or patients with siltuximab failure.